Physico-chemical and sensory characteristics of gluten free cookies containing flaxseed flour and enriched with fiber (Research, Society and Development, 2020)
People with celiac disease have difficulties in adopting a completely gluten free diet with nutritional quality. Thus, the aimed of this study to produce gluten free cookies enriched with prebiotic fibers and containing different flaxseed flour concentrations in partial replacement of rice flour. For that, four treatments were prepared with concentrations of 5%, 10%, 15% and 20% of flaxseed flour. The analysis of technological characteristics, color and sensory evaluation were carried out. The flaxseed flour addition 15% decreased (p